2015
DOI: 10.1016/j.bbmt.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxic Function of Natural Killer and CD3+CD56+ Cells in Cord Blood after Culture

Abstract: Rate of immune reconstitution (IR) directly correlates with the number of hematopoietic stem cells (HSC) infused and is particularly delayed in patients undergoing cord blood (CB) transplantation (CBT). Methods to increase the number of CB natural killer (NK) cells have the potential to improve IR after CBT. NK cells are the first lymphocyte population to recover after HSC transplant and are central to preventing early relapse and infection. CB NK cells are low in number and are known to be incomplete in matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…In addition, expanded CB-NK cells demonstrate anti-tumor activity, both in vitro and in vivo [7,8,15]. Further study of these cells has demonstrated that despite log-fold expansion, CB-NK cells are not exhausted and probably function through NKG2D [16].…”
Section: Cb-derived Nk Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, expanded CB-NK cells demonstrate anti-tumor activity, both in vitro and in vivo [7,8,15]. Further study of these cells has demonstrated that despite log-fold expansion, CB-NK cells are not exhausted and probably function through NKG2D [16].…”
Section: Cb-derived Nk Cellsmentioning
confidence: 95%
“…These techniques generally involve a 2-to 4-week cell culture in the presence of interleukin (IL)-2. Additional factors to stimulate NK cell growth include IL-15 [7], artificial antigenpresenting feeder cells [8] and FLT3 ligand [9,10]. Whereas many of these expansions arise from CB mononuclear cells (CMNCs), NK cells can also be differentiated and expanded from CD34 þ cells selected from the CB unit [11e14].…”
Section: Cb-derived Nk Cellsmentioning
confidence: 99%
“…Autologous as well as allogeneic NK cells can be purified from peripheral blood apheresis products or obtained from umbilical cord blood (UCB) [18,19]. Additionally, NK cells can be developed from CD34 + UCB stem cells or from induced pluripotent stem cells [20,21].…”
Section: Nk Cell Expansionmentioning
confidence: 99%
“…Ex vivo expansion methods included single cytokines or cytokine cocktails containing IL-2, IL-15, IL-12 or IL-18 [18,26]. To potentiate proliferation, anti-CD3 antibodies were added to cultures [27].…”
Section: Nk Cell Expansionmentioning
confidence: 99%
See 1 more Smart Citation